(2) Adverse Economic Effects Resulting from Israeli Aggressions and Continued Occupation of Egyptian Territories الآثار الاقتصادية السلبية الناجمة عن العدوان الإسرائيلي واستمرار احتلال الأراضي المصرية (INP, 2025)
The appendices to Chapter III include methodological notes on the evaluation of losses for five main sectors: 1. Petroleum Sector, 2. Suez Canal Authority, 3. Agriculture and Irrigation Sector, and 4. Construction Sector. The petroleum sector consists of four subsectors: 1. Production Subsector (011), which includes companies like General Petroleum, Eastern, GAPCO, WEPCO, and Mobil Oil. 2. Oil Refining Subsector, which includes companies such as Suez, Al Nasr, and Alexandria. 3. Marketing Subsector (011), which includes companies and organizations like Petroleum Cooperative, Hier Petroleum, Mobil Oil, Euso, Caltex, and the General Petroleum Authority. 4. Transport Subsector (011), represented by the Petroleum Pipelines Co. Each of these subsectors was classified according to the Economic Activity Classification System used by the Ministry of Planning in Egypt, with notes on major losses in each subsector.